KINERJA SISTEM INFORMASI YANG DIDUKUNG OLEH MANAJEMEN PUNCAK - Sultan, Adib (Universitas Pendidikan Indonesia, 2015)
This study aimed to examine the effect of top management support and the ability of users of accounting information systems on the performance of accounting information systems using system user satisfaction measure. The methods used to collect research data is a survey method data obtained by distributing questionnaires to the respondents. Research data based on user perceptions of respondents accounting information system by 30 respondents from bank bjb Cabang Suci. In this study, the test data used method is validity, reliability testing, and classical assumption. Then multiple linear regression analysis was used to test the hypothesis. Results of multiple linear regression analysis showed that the support of top management and accounting capabilities of information systems users significant positive effect on the performance of accounting information systems either partially or simultaneously.Â